2014
DOI: 10.1039/c3nr05405e
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature CO sensor based on cataluminescence from plasma-assisted catalytic oxidation on Ag doped alkaline-earth nanomaterials

Abstract: Based on cataluminescence from plasma-assisted catalytic oxidation, a low temperature CO sensor was fabricated. With Ag doped alkaline-earth catalyst as sensing element, air as discharge gas, carrier gas and oxidant supplier, significant cataluminescence was achieved at low temperature, demonstrating a potential low-consumption and portable sensor of CO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Based on CTL from PA catalytic oxidation, with Ag-doped alkaline-earth nanomaterial as sensing element, air as discharge gas, carrier gas and oxidant supplier, significant CTL was obtained at near room temperature. Han et al [115] therefore demonstrated a low-consumption, portable CO sensor.…”
Section: Plasma-assisted Ctlmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on CTL from PA catalytic oxidation, with Ag-doped alkaline-earth nanomaterial as sensing element, air as discharge gas, carrier gas and oxidant supplier, significant CTL was obtained at near room temperature. Han et al [115] therefore demonstrated a low-consumption, portable CO sensor.…”
Section: Plasma-assisted Ctlmentioning
confidence: 98%
“…Han et al [115] made further detailed comparison with discharge gases Ar, N 2 , He and air using DBD. Based on CTL from PA catalytic oxidation, with Ag-doped alkaline-earth nanomaterial as sensing element, air as discharge gas, carrier gas and oxidant supplier, significant CTL was obtained at near room temperature.…”
Section: Plasma-assisted Ctlmentioning
confidence: 99%
“…More interestingly, this kind of emission showed the cross-reactive properties with the distinct 2 luminescent efficiencies, which have been used for the fabrication of sensor array for the fast discriminations. [17][18][19] Additionally, fast detection and discrimination of metal ions in our surroundings is significant due to their important roles in industry, life science and food chemistry, 20 and therefore many methods have been used for the detection of metal ions. [21][22][23] However the previously reported CL-based techniques normally required the addition of strong oxidants and liquid CL reagents into the system.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, as the gas concentration reduces, sensing signal produced by sensors becomes poor [23,24]; thus, an efficient approach to acquire those signals and distinguish valuable data from noise is important for gas detection. In recent years, nanomaterials and nanotechnologies have been developed rapidly, providing some new opportunities for fabricating high-performance cataluminescent gas sensors [29,30]. Thus, a series of cataluminescent gas sensors for specific applications can be designed on the basis of nanomaterials modulation.…”
Section: Challenges For Catalysis-based Gas Sensorsmentioning
confidence: 99%
“…When the target gas flows through the tube, the catalytic reaction occurs on the surface of sensing materials. The cataluminescent intensity can be monitored In recent years, nanomaterials and nanotechnologies have been developed rapidly, providing some new opportunities for fabricating high-performance cataluminescent gas sensors [29,30]. Thus, a series of cataluminescent gas sensors for specific applications can be designed on the basis of nanomaterials modulation.…”
Section: Typical Cataluminescent Detection Systemmentioning
confidence: 99%